2001
DOI: 10.1046/j.1469-7580.2001.19960675.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic origin of a sympathetic supply to the upper limb: the ‘nerve of Kuntz’ revisited

Abstract: An understanding of the origin of the sympathetic innervation of the upper limb is important in surgical sympathectomy procedures. An inconstant intrathoracic ramus which joined the 2nd intercostal nerve to the ventral ramus of the 1st thoracic nerve, proximal to the point where the latter gave a large branch to the brachial plexus, has become known as the ' nerve of Kuntz ' (Kuntz, 1927). Subsequently a variety of sympathetic interneuronal connections down to the 5th intercostal space were reported an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…In six of 12 patients, we found additional thin sympathetic chain under the clipped chain, which could not be seen without complete dissection and lifting of sympathetic chain between second and fourth ribs. Sympathetic chain variations are very important for the success rate of operation [15,16]. Surgical failure and recurrence of hyperhidrosis after operation probably may be resulted from the anatomical variations as seen in our study.…”
Section: Discussionsupporting
confidence: 50%
“…In six of 12 patients, we found additional thin sympathetic chain under the clipped chain, which could not be seen without complete dissection and lifting of sympathetic chain between second and fourth ribs. Sympathetic chain variations are very important for the success rate of operation [15,16]. Surgical failure and recurrence of hyperhidrosis after operation probably may be resulted from the anatomical variations as seen in our study.…”
Section: Discussionsupporting
confidence: 50%
“…Ramsaroop et al (2001) reported an incidence of 61%, while Chung et al, (2002) reported an incidence of 68.2%. Our study found an incidence of 40%(20/50).…”
Section: Additional Rami Communicantes and Their Implicationsmentioning
confidence: 94%
“…The first intercostal ramus or Kuntz nerve (Ramsaroop et al, 2001) (Fig. 2), connecting the second intercostal nerve to the ventral ramus of the first thoracic nerve was observed in 20 of 50 sides (40%) and was present bilaterally in 16%(4/25)of cadavers.…”
Section: Additional Rami Communicantesmentioning
confidence: 95%
“…It may also be slightly lateral within the intercostal space at the level of the intervertebral space near the upper border of the third rib [ 16,17 ] .…”
Section: Anatomymentioning
confidence: 99%